COVID-19: impact on blood and transfusion services - Leitão, Céu (2022)
A novel coronavirus emerged with an exponential and universal cycle of infection, carrying great morbidity and mortality rate. Since the patients suffer from the severe acute respiratory syndrome, the new virus designated as SARS-CoV-2, caused an outbreak and the pronouncement of a pandemic state, forcing people into isolation. The disease named Coronavirus disease 2019 (COVID-19) led to a drastic decline in blood supply and a new order of clinical transfusion proceedings management. The Portuguese Blood and Transplantation Institute with the other national responsible organizations formulated a normative contingency plan, in order to ensure and maintain a safe blood component support to all hospital requests. Regardless of the safety policies applied systematically in the transfusion process, such as routine nucleic acid tests in all donations, leukoreduction and pathogenic inactivation of blood components, the incomplete knowledge about the epidemiology and pathogenicity of SARS-CoV-2 suggests the precautionary principle. This lesson learned from previous outbreaks is a mandatory instruction in the transfusion medicine sector. Assuming the absence of vaccines and specific medication, reference laboratories of Blood and Transplantation Centers, Blood Functional Area, are intensively tagging the identification and screening of potential donors COVID-19 convalescent plasma as an alternative therapy.